Democratic Republic of Congo : Product and Market Concentration and the Vulnerability to Exogenous Shocks - Bou-Habib, Chadi; Kebede, Ephraim (World Bank, Washington, DC, 2016)
The high level of exports and their product and market concentration exposes the Democratic Republic of Congo to the economic fluctuations of the country's trade partners. This paper uses the United Nations Conference on Trade and Development trade data set to analyze the Democratic Republic of Congo's export patterns for the period 1960-2014. The data confirm that the country's exports remain highly concentrated. The product concentration on minerals is high and reaches exceptional levels. The geographic concentration is also high, while there is a shift in destinations. Hence, EU27, traditionally the main market destination for the Democratic Republic of Congo, lost its importance to China for most of the past decade. This trend continued to increase in the past few years from 2010 to 2013. The clear prevalence of commodity products within the Democratic Republic of Congo's exports and the higher exposure to the Chinese economic cycle are sources of vulnerability. The empirical analysis indicates that the country's exports appear to be significantly sensitive to foreign demand fluctuations. This exposure increases the volatility of the country's macroeconomic framework to exogenous shocks, with negative consequences on growth in gross domestic product and on external balances. The analysis concludes that increasing the Democratic Republic of Congo's resilience requires product and market diversification of exports. This diversification requires improvements in the investment climate and business environment, with emphasis on skills and infrastructure.